Perceptions of nursing students regarding their Discipline at Kabul University of Medical Science in 2021 - Ahmadi, Abdul Qudoos; Faizi, Najeebullah; Hamidi, Sayed Obaidullah; Majidi, Hafizullah (Technium Social Sciences Journal, 2022)
Abstract Background and Aim: Students' perspectives regarding their Discipline directly affect the quality and quantity of health care and ultimately the health of individuals and society. This study aimed to determine the perspective of Nursing Students at Kabul University of Medical Sciences “Abo Ali ibn Sina” about their Discipline. Methodology: A cross-sectional descriptive study was conducted among 249 nursing students at Kabul University of Medical Sciences “Abo Ali ibn Sina” by census sampling method. The data collection tool was the University of Minnesota Questionnaire based on the Likert scale. Data were coded and analyzed using Statistical Package for Social Science (SPSS25) software. Results: The mean and standard deviation of the student's perspectives regarding their Discipline were 15.85 ± 4.777 respectively, which was higher than the mean exam score. In total, 143 (57.4%) participants had positive perspectives regarding their Discipline, 78 (31.3%) had negative perspectives And 28 (11.2%) were neutral. According to the results of the Kruskal-Wallis test, Perceptions of Nursing students regarding their Discipline had a statistically significant difference between marital status (P=0.005), Accommodation type (P = 0.028), and classes (P=0.001). Conclusion: The mean score for the perspectives of the population under investigation toward their Discipline was higher than the acceptable level which demonstrates a desirable perspective toward their Discipline among the majority of students.